VERBAL FLUENCY TASK PERFORMANCE IN PERSONS WITH MODERATE INTELLECTUAL DISABILITY - Gligorović, Milica; Buha, Nataša; Dučić, Bojan; Kaljača, Svetlana (Specijalna edukacija i rehabilitacija, 2018)
Verbal fluency is an indicator of the executive functions and mental lexicon. The aim of this paper is to determine phonemic and semantic productivity in persons with moderate intellectual disability (ID). The sample consisted of 58 persons with moderate ID, aged 15-25. Phonemic fluency was assessed by the Controlled Oral Word Association Test, while the Category Naming Test (CNT) was used to assess semantic fluency. The performance in the semantic fluency task was significantly better than the results on the phonemic fluency task. IQ was a significant factor of both assessed aspects of verbal fluency, but participants’ age had a greater individual influence on semantic productivity and higher predictive value than IQ. We can conclude that maturation and experience represent significant factorsin forming lexical-semantic network, but they do not significantly contribute to the potential of persons with moderate ID for generating and using non-routine strategies. Intervention programs should offer a wider repertoire of strategies and more creative approach in strategy generation, organization and manipulation. Key words: moderate intellectual disability, verbal fluency, phonemic fluency, semantic fluency, executive functions